NCMP-23. PEMBROLIZUMAB-ASSOCIATED CD8+ VASCULITIC MONONEURITIS MULTIPLEX IN A PATIENT WITH MESOTHELIOMA: FIRST CASE REPORT. (9th November 2020) - Baldauf, Michaela; Monika, Kapauer; Markus, Jörger; Lukas, Flatz; Rodriguez, Regulo; Frank, Stephan; Felbecker, Ansgar; Thomas, Hundsberger
Abstract: INTRODUCTION: Immunotherapy, especially with immune checkpoint inhibitors (ICPI), has increasingly become an attractive treatment modality for various types of cancers. However, many patients develop ICPI-associated autoimmune adverse events such as pneumonitis, colitis or rarely neurological syndromes. Large and medium vessel vasculitis haS only occasionally been reported. Here we report the first case of ICPI-associated mononeuritis multiplex in a patient with malignant mesothelioma, caused by a histological proven small vessel vasculitis. CASE REPORT: A 61-year old female developed subacute progressive painful and asymmetric sensorimotor deficits on distal extremities. Electrophysiologically, signs of a severe axonal neuropathy of both legs and the right arm were found, and swellings of the corresponding nerves were seen upon nerve ultrasound exam. The clinical and electrophysiological findings were reminiscent of mononeuritis multiplex. Laboratory work up including CSF examination was normal. More than two years prior to developing peripheral nerve deficits, the patient had been diagnosed with malignant pleural mesothelioma and treated with the anti-PD1 monoclonal antibody pembrolizumab on progression after chemotherapy. Biopsy of the right sural nerve revealed a small vessel vasculitis with a lymphocyte predominance of CD8+ T cells over CD4+ T as well as B lymphocytes. Despite discontinuation of pembrolizumab and immunosuppressive treatment (high dose methylprednisone, cyclophosphamide) complemented by opioid therapy, painful allodynia persisted. CONCLUSION: ICPI-associated autoimmune disorders also include small vessel vasculitis with rare phenotypes such as mononeuritis multiplex. Further studies are required to improve our understanding of the link between ICPIs, and the pathogenic process leading to vasculitis, as well as to optimize treatment options for those rare diseases.